The role of monocytes in angiogenesis and atherosclerosis - Jaipersad, Anthony S; Lip, Gregory Y H; Silverman, Stanley; Shantsila, Eduard (Journal of the American College of Cardiology, 2014)
New vessel formation inside the arterial wall and atherosclerotic plaques plays a critical role in pathogenesis of heart attacks and strokes. The 2 known mechanisms resulting in the formation of new vessels within the plaque are local ischemia and inflammation. Blood monocytes play an important role in both processes. First, they express receptors for vascular endothelial growth factor and some of them may serve as circulating ancestors of endothelial cells. Second, monocytes are associated with inflammation by synthesis of inflammatory molecules following their activation (e.g., after stimulation of Toll-like receptors). Neovascularization is a reparative response to ischemia, and includes 3 processes: angiogenesis, arteriogenesis, and vasculogenesis. Angiogenesis, the formation of new capillary vessels is known to occur in response to a hypoxic environment. The interaction between leukocytes and vascular wall via overexpression of various molecules facilitates the migration of inflammatory cells into the plaque microenvironment. Monocytes are intimately involved in tissue damage and repair and an imbalance of these processes may have detrimental consequences for plaque development and stability. Importantly, monocytes are comprised of distinct subsets with different cell surface markers and functional characteristics and this heterogeneity may be relevant to angiogenic processes in atherosclerosis. The aim of this review article is to present an overview of the available evidence supporting a role for monocytes in angiogenesis and atherosclerosis.